State filling phenomena in modulation-doped InAs quantum dots - Park, YM; Park, YJ; Kim, KM; Shin, JC; Song, JD; Lee, JI; Yoo, KH (ELSEVIER SCIENCE BV, 2004)
We have investigated the electrical and optical properties of the modulation-doped InAs quantum dots (QDs) by alternately supplying In and As sources. Three different samples are fabricated according to the doping concentration of the Si-doped GaAs layer. All the samples show the excited state emissions as well as the ground state emission in photoluminescence (PL) spectra due to the state filling by the electrons supplied from the doped GaAs layer. For a low doping concentration the transition from the first excited electron state to the first excited hole state (E1-H1) is apparent together with the ground state transition (E0-H0). These PL emissions increase with the similar rate as the excitation power density increases. For higher doping concentrations the ground state transition and the transition from the first excited electron state to the ground hole state (E1-H0) are apparent at a low excitation power density. As the excitation power density increases, the E1-H1 transition becomes dominant rather than the E1-H0 transition. In the capacitance-voltage (C-V) result for the sample with a low doping concentration, the characteristic steps due to the accumulation of electrons are observed. For the sample with higher doping concentrations the characteristic step is not found in C-V curves, which is associated with the state filling of QDs. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: TIME-RESOLVED PHOTOLUMINESCENCE; FERMI-EDGE SINGULARITY; ISLANDS; CARRIER; HETEROSTRUCTURES; INGAAS; GROWTH; LEVEL; GAAS